Gentrification and violent crime in New York City - Barton, Michael S. (Crime & delinquency, 2016)
Research has frequently referenced the influence of gentrification on crime, but only a few studies empirically assessed this relationship. Recent research has utilized innovative measures of gentrification and advanced statistical techniques, but many questions remain unanswered. One such question is whether and to what extent gentrification influenced crime in New York City. The current study used a quantitative operationalization of gentrification that was grounded in qualitative information and hybrid fixed-effects regression to assess whether changes in violent crime rates in New York City were associated with gentrification. Results indicate that sub-boroughs that experienced greater rates of gentrification featured significantly larger declines in assault, homicide, and robbery and that this relationship did not vary significantly over time.